(untitled) (Research, Society and Development, 2023)
Objective: to evaluate the trend in the infant mortality rate from preventable causes in the State of Amapá in the period 2010-2019. Methods: This is a descriptive time series study based on data available in the Mortality Information System (SIM) and in the Live Births Information System (SINASC). For the analysis of temporal trends, the linear regression model was used. Results: in the decade, there were 2,935 infant deaths registered in the State, 72.67% (n=2,133) of which were preventable. The infant mortality rate found was 18.97; there was an increasing trend in the rate of post-neonatal deaths, a decreasing trend in the rate of preventable infant deaths and an increase in deaths that could be prevented by adequate care for pregnant women. Conclusion: although the infant mortality rate has reduced in Amapá (2010-2019), this indicator remains high compared to national averages. Our data point to the need for more effective health strategies aimed at pregnant women in the region.